QUANTITATIVE TRACE ELEMENT ANALYSIS OF SINGLE FLUID INCLUSIONS BY PROTON-INDUCED X-RAY EMISSION (PIXE): APPLICATION TO FLUID INCLUSIONS IN HYDROTHERMAL QUARTZ - Kurosawa M.; Shimano S.; Ishii S.; Shima K.; Kato T. (My University, 2003)
Single fluid inclusion analogues with known elemental composition and regular shape were analyzed for trace element contents by particle-induced X-ray emission (PIXE)-a nondestructive method for the analysis of single fluid inclusions-to evaluate the accuracy and detection limits of this type of analysis. Elements with concentrations of 10 to 1000 ppm were measured with average estimated relative error of +/-7%. For natural fluid inclusions with 30 μm radius and 20 μm depth in quartz, the total analytical errors were estimated to be +/-40% relative for Ca, +/-16% for Fe, +/-13% for Zn, +/-12% for Sr, and +/-11% for Br and Rb, by considering uncertainties in microscopic measurements of inclusion depths. Detection limits of 4 to 46 ppm for elements of mass numbers 25-50 were achieved for analyses of a spherical fluid inclusion with 30 μm radius and 20 μm depth in quartz, at an integrated charge of 1.0 μC. The trace element compositions of single fluid inclusions in a hydrothermal quartz crystal were also determined. The elemental concentrations in the inclusions varied widely: 0.2-9 wt.% for Ca and Fe, 300-8000 ppm for Mn and Zn, 40-3000 ppm for Cu, 100-4000 ppm for Br, Rb, Sr, and Pb, and less than 100 ppm for Ge. Elemental concentrations of secondary fluid inclusions on the same trail varied over an order of magnitude, even though all these inclusions were formed from the same fluid. Elemental concentrations in inclusions on the same trail are positively correlated with each other, except for Cu and Rb. Ratios of almost all elements in the inclusions on the trail were essentially unchanged; thus, the elemental ratios can provide original information on trace element compositions of a hydrothermal fluid.